Cytokine expression of soft tissue cells cultured with titanium discs and their respective supernatants in vitro - dos Santos Sanches, Natália [UNESP]; Panahipour, Layla; Wang, Lei; Imani, Atefe; Marchiolli, Caroline Liberato [UNESP]; Cervantes, Lara Cristina Cunha [UNESP]; Stein, Maria Cristina Ruiz Voms [UNESP]; Berton, Sara Alves [UNESP]; Souza, Francisley Ávila [UNESP]; Okamoto, Roberta [UNESP]; Júnior, Idelmo Rangel Garcia [UNESP]; Gruber, Reinhard (Springer Nature, 2025)
Objective: Titanium surface modifications improve osseointegration in dental and orthopedic implants. However, soft tissue cells can also reach the implant surface in immediate loading protocols. While previous research focused on osteogenic cells, the early response of soft tissue cells still needs to be better understood. Material and methods: We have established a bioassay to this aim where human gingival fibroblasts, HSC2 oral squamous carcinoma cells, and murine bone marrow cells were cultured onto titanium discs or exposed to the respective supernatants for overnight. Modifications were double acid-etching (SLA), and coating with simulated body fluid (SBF) with or without odanacatib (ODN), a selective cathepsin K inhibitor reducing bone resorption. Results: Our findings indicate that direct contact with titanium discs, with all surface modifications, slightly reduces cell viability. Growing gingival fibroblasts on discs consistently showed a trend toward increased IL8 expression. In HSC2 cells, this setting significantly increased IL1 and IL8 expression, confirmed by the immunoassay. Murine bone marrow macrophages also showed an increase in IL1 and IL6 expressions. Supernatants of the respective discs failed to cause these changes. Although ODN coating inhibited cathepsin K, osteoclastogenesis remained unchanged. Conclusions: These findings suggest that titanium discs do not provide a favorable in vitro surface for oral soft tissue cells as they lose viability and respond with a moderately increased expression of inflammatory cytokines. Clinical relevance: The soft tissue surrounding a dental implant can impact rehabilitation success. Understanding how soft tissue cells respond to titanium surface is potentially relevant to understand clinical outcomes.
Keywords: Cell culture techniques; Inflammatory response; Odanacatib; Simulated body fluid; Supernatant; Titanium disc